Application of Clitoria ternatea L. Flower Extract Lotion in Preventing the Decrease in Collagen and Epidermis Thickness in Wistar Rats Skin Given Ultraviolet-B Rays - Ira Gracela; Ermi Girsang; Ali Napiah Nasution; Jeri Yuliansyah; Riri Virzan Putri (Jurnal Penelitian Pendidikan IPA, 2025)
Exposure to ultraviolet-B (UV-B) light contributes to a decrease in skin collagen levels, which can cause premature aging. This study aims to evaluate the effectiveness of telang flower (Clitoria ternatea L.) extract lotion in maintaining collagen levels and epidermal thickness of UV-B-exposed rat skin. A total of 30 Wistar male white rats (200-250 g) were divided into six treatment groups: negative control (distilled water), positive control (Vaseline), and four treatment groups of telang flower extract lotion with concentrations of 0.2, 0.5, 0.75, and 1%. Mice were exposed to UV-B light (311 nm, 70 mJ/cm² per session) for 14 days with a total dose of 420 mJ/cm². The lotion was applied twice daily, before and after UV-B exposure. Evaluation was performed by measuring collagen content and epidermal thickness using histology staining. Statistical analysis used One-Way ANOVA or Kruskal-Wallis if assumptions were not met. The results showed that the treatment group with telang flower extract significantly increased collagen content and epidermal thickness compared to the negative control (p < 0.05), with a dose of 0.5% showing the highest effectiveness. In conclusion, telang flower extract lotion has potential as a photoprotective agent against UV-B-induced skin damage.